The effects of clearing and cropping on the organic reserves and biomass of tropical forest soils - Ayanaba, A.; Tuckwell, S.B.; Jenkinson, D.S. (1976)
Twenty Nigerian soil samples, mainly from field experiments at the International Institute of Tropical Agriculture (IITA), were used in a study of the effects of clearing and cropping on the C, N and S reserves of soils under secondary lowland rain forest. Soils that had been cropped for 2yr usually contained less total C and N than the corresponding forest soils. This decline was less rapid when crop residues (maize) were returned to the soil as a mulch than when they were removed.